The effect of gender on individual anaerobic treshold in swimming: A comparison between relative and absolute parameters - Pelarigo, J.; Sousa, A.; Ribeiro, J.; Cascais, C.; Denadai, B.; Greco, C.; Fernandes, R.; Vilas Boas, J. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Some of the major sports performance determinant factors have been shown to be dependent on gender characteristics. Anaerobic threshold for instance is influenced by anthropometric, hormonal and genetic differences (Thibault, et al., 2010). However, researchers usually used absolute values to compare such differences, whereas relative analysis is scarce. The purpose of this study was to examine the effect of gender on absolute and relative individual anaerobic threshold (IAnT) in swimming. Methods: Eight males (18.5 ± 3.1yr, 1.79 ± 0.05m, 72.1 ± 7.0kg) and 8 females (17.6 ± 2.1yr, 1.69 ± 0.04m, 59.6 ± 4.8kg) middle and long-distance swimmers, with similar mean relative performances over a 400m freestyle swim (88.2 ± 3.4% and 88.4 ± 2.7%, of the 25m WR, respectively) participated in this study. The swimmers performed a 7 x 200m front crawl incremental protocol until voluntary exhaustion (Fernandes et al., 2006) to determine the velocity (v) associated to IAnT and V.O2max. Blood lactate concentration [La-], V.O2 and heart rate (HR) were controlled during the test. The data were analyzed using one way ANOVA (p<0.05). Results: The absolute IAnT values showed significant differences for v (1.34 ± 0.07 and 1.24 ± 0.06m/s), [La-] (2.0 ± 0.5 and 1.5 ± 0.5mmol/L), and HR (162 ± 9 and 172 ± 8bpm) for males and females, respectively. However, V.O2 at the IAnT (50.2 ± 5.9 and 46.7 ± 4.7 mL/kg/min) was similar. Regarding relative IAnT values expressed as a percentage of V.O2max, V.O2 (84.1 ± 7.3 and 82.8 ± 5.4%), v (91.2 ± 3.6 and 90.5 ± 3.4%), [La-] (22.5 ± 4.3 and 22.8 ± 7.4%), and HR (89.3 ± 3.9 and 90.8 ± 3.1%) showed similar values between genders. Discussion: Commonly, the scientific literature demonstrates gender differences on factors related to performance, such as the absolute variables presented in the present study. However, those variables, such as IAnT related physiological and biomechanical parameters, when expressed as a percentage of V.O2max, showed similar values. Thus, coaches and researchers may apply the same relative IAnT parameters when expressed as a percentage of V.O2max for training control and prescription in male and female swimmers.